1. THE ROLE OF AIR POLICING IN ACHIEVING AIR SUPERIORITY: AN ANALYSIS WITH NATO AIR POLICING CASE STUDY - Andri Gandhy; Suroso; Andri; Kurniawan; Dikatama Tsania; Furqon (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
Air policing serves as a critical mechanism for maintaining airspace integrity within nations or alliances, directly contributing to air superiority in military defense contexts. This paper analyzes the role of air policing in establishing and sustaining air dominance, focusing on the NATO Air Policing case study. Employing qualitative and quantitative approaches, including literature review, historical data, statistical tables, and graphs, we explore how air policing functions as deterrence, rapid response, and a foundation for broader military operations. The NATO case since 2004 demonstrates over 300 annual interceptions in recent periods, reinforcing alliance solidarity and preventing conflict escalation. In-depth analysis, enhanced by Analytic Hierarchy Process (AHP) for prioritizing factors, Monte Carlo simulations for risk assessment, and relevant theories such as deterrence theory and air power theory, reveals air policing as a strategic element supporting modern military doctrines where air superiority is prerequisite for ground and naval operations. Findings emphasize the integration of advanced technologies like radar and fifth-generation fighters to enhance effectiveness. This paper concludes that air policing is a foundational pillar for air superiority, with implications for global defense policies in geopolitical tensions.